The development of the romantic rival in Ovid's Heroide 5: Helen through oenone's enunciative voice (Argos, 2022)
In this paper we address the figure of Helen as a romantic rival in Heroide 5, which is attributed —at a fictional level— to Oenone by Ovid. By analysing different lexemes and syntagms, we will try to show that the enunciative voice develops a story to enhance her image and persuade the hero to return. Additionally, and contrastingly, she uses terms that question the moral qualities, trustworthy nature, and marital duties of her rival to judge her actions, holding Helen responsible for the abandonment. We will also show how the voice of Oenone does not merely present the rival as the cause of personal, but also collective misfortune (the suffering of peoples and heroes), in accordance with the net of intra and intertextual references operating around the figure of Helen in the literary tradition.
Keywords: Ovidian intertextuality; Heroides; Love rivalry; Oenone; Helen